Etiology and treatment of osteonecrosis of the mandible - Bast, Florian; Groß, Andreas; Hecht, Lars; Schrom, Thomas (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : Post-radiogenic osteonecrosis of the mandible is a serious complication in patients with combined treated head/neck tumors. Osteonecrosis of the mandible can also occur following administration of bisphosphonates. In the present article we would like to present our experiences over the last five years in treating both bisphosphonate-associated osteonecrosis and osteoradionecrosis. Material and methods : Of the patients treated in our hospital for bone necrosis of the mandible between January 2005 and June 2010, 16 were diagnosed with infected osteoradionecrosis and 10 with bisphosphonate-associated osteonecrosis. The patients with osteoradionecrosis were administered the classic osteomyelitis treatment. The same procedure was carried out on 5 of the 10 patients with bisphosphonate-associated osteonecrosis; the remaining 5 were treated conservatively due to advanced bone infection. The bone biopsies and specimens of both entities yielded by the surgical interventions were examined histologically after decalcification. Results : Of the 16 patients treated for infected osteoradionecrosis, 7 recovered after decortication and long-term antibiosis. In 7 cases consolidation did not occur until after osseous continuity resection. In 2 cases the progress of the intraosseous infection could not be stopped with treatment. A typical first symptom of bisphosphonate-associated osteonecrosis was an alveolus that would not heal after a tooth extraction. In 50% of patients with bisphosphonate-associated osteonecrosis recovery was successful with a combination of surgery and long-term antibiosis. In the other patients with advanced bisphosphonate-associated osteonecrosis no definitive cure for the infection of the necrotic bone was possible. Conclusion : In terms of treatment, osteoradionecrosis proves complex, yet easier to treat than bisphosphonate-associated osteonecrosis. The removal of the infected bone tissue is often necessary, but it does not always lead to recovery. Therefore it can be concluded that prevention of intraosseous infection by consistent pretherapeutic dental hygiene is especially important.